Pengaruh Promosi Terhadap Minat Beli Produk Fashion di Aplikasi Tiktok (Studi Kasus pada Mahasiswa Universitas Teuku Umar) - Zeninta, Zeninta; Rahmadhani, Eva Putri; Manan, Afni Abdul (PENG: Jurnal Ekonomi dan Manajemen, 2025)
In the current era of globalization, online shopping is very popular among people, because they indirectly follow increasingly changing lifestyles. Like using TikTok as a medium for online shopping. Tiktok also provides promotions that attract the attention of consumers, including students, who are easily tempted by these offers. This research aims to find out how much influence promotions on the Tiktok application have on UTU students' buying interest in buying fashion products. This research also aims to find out how much influence arises after learning about promotions on the Tiktok application. The method applied in this research is a quantitative approach using analytical techniques. simple regression data using help from the SPSS program. The findings of this research are that the R-Square coefficient of determination is 54.4%. This means that the influence of promotion on interest in buying fashion products is 54.4% and 45.6% is the influence of other variables.